FORMATION OF RUSSIAN NATIONAL IDENTITY OF HIGH SCHOOL STUDENTS: HERMENEUTICAL APPROACH - Alfia F. Zakirova; Larissa A. Semenova (Obrazovanie i Nauka, 2015)
The purpose of the article is the description of means and methods of formation of a Russian national identity (RNI), one of which is the organization of joint collective students’ activities on formation of skills of interpretation of a human behavior as a text event in the context of ethnic culture of a student in order to find common Russian collectivist values, their rethinking in terms of a search of the general national identity and the comprehension of the other on the basis of some cultural differences.Methods. The means of formation of a Russian national identity at the stage of self-identification of students with Russian values and norms of interaction is offered a hermeneutic approach which is based on the ideas of hermeneutics as the art of understanding of someone else’s identity, the inner world of a man and the «empathy» in another person in order to eliminate the semantic «barriers» in the communicative activity of learners. It is directed to the understanding of subjects of the educational process as the bearers of ethnic cultures through dialogue and finding the universal general national values. The methods of the techniques of a script, scenario requirements (a text as a source of a script for reflection and dialogue) and the role of expectations (presentation to a learner of algorithm of expected behavior from him in order to achieve mutual understanding in interaction) are used in the course of experimental investigations.Results. It is proved that the awareness of participants of the educational process in norms and values and their reinterpretation in the aspect of the search for a general national identity is able not just to make «expressible» some installations of the subject, but also can significantly affect his worldview, to make him more reliable and predictable partner of a social interaction. The basis of this outlook is the dialectics of thinking, the simultaneous vision of individual and social, ethnic and civil plans of consciousness and behavior.Scientific novelty. Ethnic behavior is characterized as a social and cultural phenomenon and a cultural text event. Valid, benevolent interpretation of ethnic behaviour, search of universals in its semantic filling helps to remove the semantic barriers, disturbing joint activity. Psycho-pedagogical mechanism of a meaning is disclosed. The hermeneutic approach is implemented as an imposition in an external plan and verbalization of characteristics of identity, norms and values, adopted by the participants of the educational process.Practical significance. A specially organized educational work via text mediation and collective joint activity contributes to the development of individual consciousness of students and provides: grasp a sense of community with the peoples of Russia; self-identification with Russian values and traditions; harmonization of ethnic and civil identity and behavior plans; development a sense of duty, responsibility, and active love for the country.